Modeling and parametric analysis of a small scale trigeneration system - Shyam Suresh Krishnan. (2010)
The field of Energy engineering has made significant process today, moving towards and integrated and holistic approach. Increasing energy demand and stringent emission standards has increased the importance of energy system modeling and simulation. A trigeneration system enables the simultaneous production of heating, cooling and power, and can be generally categorized under integrated energy systems. An integrated energy system is applicable where different forms of energy services are in demand, e.g. a building which requires electricity, space heating as well as cooling loads. For such an application of trigeneration system is appropriate and can also realize substantial energy/cost savings.